Improvements in Diabetes Control Similar in Patients Who Undergo LAGB or Intensive Management - Shuman, Jill (MD Conference Express, 2015)
Laparoscopic gastric banding and an intensive nonsurgical intervention appear to provide similar outcomes among patients who are obese with type 2 diabetes mellitus. At 1 year, patients who underwent gastric banding lost more weight than those who had no surgery, but no significant differences were seen in HbA1c, fasting blood sugar, or other cardiometabolic measures.